Exploring Student Engagement Predictors for Working Students: The Role of Self-Esteem and Social Support with Resilience As Mediator - Rahayu, Anizar; Fachmi, Teguh; Burhanudin, Mohammad Daffa (Islamic Guidance and Counseling Journal, 2024)
This research uses structural equation modelling (SEM) technique to investigate and comprehend the dynamics of student engagement among working students, with a particular emphasis on the effects of self-esteem and social support mediated by resilience. It also aims to discover the complex relationships between those variables and to identify the mechanisms that help to improve student engagement. Total numbers (n)=340 working students were taken as sample, self-report questionnaire was applied. Research known that self-esteem don’t affect student engagement directly, but indirect results of the study showed that resilience significantly mediated the relationship between self-esteem and student engagement. Social support also had a significant direct effect on student engagement, and resilience significantly mediated the relationship between social support and student engagement.